Vestibular attenuation to random-waveform galvanic vestibular stimulation during standing and treadmill walking - Kelci B. Hannan (Nature Portfolio, 2021)
Abstract The ability to move and maintain posture is critically dependent on motion and orientation information provided by the vestibular system. When this system delivers noisy or erred information it can, in some cases, be attenuated through habituation. Here we investigate whether multiple mechanisms of attenuation act to decrease vestibular gain due to noise added using supra-threshold random-waveform galvanic vestibular stimulation (GVS). Forty-five participants completed one of three conditions. Each condition consisted of two 4-min standing periods with stimulation surrounding a 1-h period of either walking with stimulation, walking without stimulation, or sitting quietly. An instrumented treadmill recorded horizontal forces at the feet during standing and walking. We quantified response attenuation to GVS by comparing vestibular stimulus-horizontal force gain between conditions. First stimulus exposure caused an 18% decrease in gain during the first 40 s of standing. Attenuation recommenced only when subjects walked with stimulation, resulting in a 38% decrease in gain over 60 min that did not transfer to standing following walking. The disparity in attenuation dynamics and absent carry over between standing and walking suggests that two mechanisms of attenuation, one associated with first exposure to the stimulus and another that is task specific, may act to decrease vestibulomotor gain.